THE ROLE OF POLITICAL INFLUENCERS AND DIGITAL CAMPAIGNERS IN BUILDING LONG-TERM VOTER LOYALTY IN INDONESIA AFTER THE 2024 ELECTION - Azhar Hutomo,; Romi Syahril,; Priatna,; A.Rafiq, (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2025)
This study aims to understand the role of political influencers and digital campaigners in shaping long-term loyalty among young Indonesian voters post-2024 elections. Using a qualitative approach through case study methods and digital content analysis, this study examines the communication styles, political narratives, and personal interactions of influencers through social media in shaping sustainable political perceptions. The analysis shows that political influencers are able to form significant emotional and cognitive attachments with voters through educational and interactive content. The resulting voter loyalty depends not only on affiliation with political parties or political ideology, but also on the credibility and consistency of the influencer's communication. These findings demonstrate a shift in the dynamics of contemporary political communication and the importance of strengthening digital political literacy post-campaign.